Design and fabrication of orange peeler / Muhammad Danial Nakhaie Mohd Zamri - Mohd Zamri, Muhammad Danial Nakhaie (2022)
Current objects are progressively being replaced by new and improved products because of greater competition and technological advancement. However, without ergonomic design, which guarantees that people and employees are at ease and safe while performing their jobs, innovation is insufficient. Large-scale orange peeling will require a lot of alborada and take a lot of time. Additionally, peeling oranges with an outdated press carries some hazards, such as finger injuries to the user. because people have become more creative in making places where others can work more easily and safely. This project is more concerned with the design and manufacture of an orange peeler.